In vitro activity profiling of Cumyl‐PEGACLONE variants at the CB1 receptor: Fluorination versus isomer exploration. Issue 9 (3rd July 2020) - Janssens, Liesl; Cannaert, Annelies; Connolly, Matthew J.; Liu, Huiling; Stove, Christophe P.
Abstract: Synthetic cannabinoid receptor agonists (SCRAs) are one of the largest groups of new psychoactive substances monitored in Europe. SCRAs are known to typically exert higher cannabinoid activity than tetrahydrocannabinol from cannabis, thereby entailing a greater health risk. Both Cumyl‐PEGACLONE and 5F‐Cumyl‐PEGACLONE were not controlled by the national legislation upon their first detection in Germany in 2016 and 2017, respectively, and have been linked to several fatalities. In this study, the CB1 receptor activity of these compounds, together with two newly synthesized structural isomers (Cumyl‐PEGACLONE ethylbenzyl isomer and n ‐propylphenyl isomer), was assessed using two different in vitro receptor‐proximal bioassays, monitoring the recruitment of either β‐arrestin2 (β‐arr2) or a modified G protein (mini‐Gαi ) to the activated CB1 receptor. In terms of both potency and relative efficacy, Cumyl‐PEGACLONE and 5F‐Cumyl‐PEGACLONE were found to exert strong CB1 activation, with sub‐nanomolar EC50 values and efficacy values exceeding those of the reference agonist JWH‐018 threefold (β‐arr2 assay) or almost twofold (mini‐Gαi assay). The ethylbenzyl and n ‐propylphenyl isomers exhibited a strongly reduced CB1 activity (EC50 values >100 nM; efficacy <40% relative to JWH‐018), which is hypothesized to originate from steric hindrance in the ligand‐binding pocket. None of the evaluated compounds exhibited significant biased agonism. In conclusion, the functional assays applied here allowed us to demonstrate that 5‐fluorination of Cumyl‐PEGACLONE is not linked to an intrinsically higher CB1 activation potential and that the ethylbenzyl and n ‐propylphenyl isomers yield a strongly reduced CB1 activation. Abstract : The cannabinoid activity of Cumyl‐PEGACLONE, its 5‐fluorinated analogue and two structural isomers was assessed in two in vitro CB1 activation bioassays. Whereas 5F‐Cumyl‐PEGACLONE exhibited a high potency and efficacy, the ethylbenzyl‐ and n ‐propylphenyl isomers had a strongly reduced CB1 activity.